Obstetric Risk Factors and Serological Characteristics of Early-Onset Neonates Bacterial Infections - Wang, Yuejiao; Chen, Qi; Xu, Shixia; Chao, Shuang (Frontiers in Surgery, 2022)
Purpose: To analyze the obstetric high-risk factors and serological characteristics of early-onset neonatal bacterial infections (EONBI). Methods: 119 neonates with early-onset bacterial infection who were admitted to the neonatal ward of our hospital from October 2020 to December 2021 were recorded as the study group, and 100 neonates without bacterial infection who were admitted during the same period were used as the reference group. Comparative analysis of obstetric high-risk factors and serological characteristics of EONBI. Results: There was no statistical difference between the two groups in terms of gender and age at admission (P>0.05). The gestational age and birth weight of newborns in the study group were lower than those in the reference group (P<0.001). Univariate analysis showed that preterm birth, unexplained asphyxia, fecal contamination of amniotic fluid, maternal infection during pregnancy, and premature rupture of membranes ≥18h were significantly associated with EONBI (P<0.05); while there was no significant difference between the two groups in the comparison between diabetic mother and child and maternal fever at delivery (P>0.05). Multifactorial analysis showed that preterm birth, fecal contamination of amniotic fluid, maternal infection during pregnancy, and premature rupture of membranes ≥18h had a good multivariate dependence on EONBI (P<0.05), while there was no significant association with unexplained asphyxia, diabetic mother and child, and maternal fever at delivery (P>0.05). The incidence of neonatal temperature >37.9°C was higher in the study group than in the reference group (P<0.05), and there were no statistical differences in the comparison of other clinical manifestations (P>0.05). The CRP level of neonates in the study group (47.33±4.14) mg/L was higher than that of the reference group (4.84±1.03) mg/L (P<0.001). The WBC level of neonates in the study group (5.64±1.18) × 109/L was higher than that of the reference group (0.28±0.04) × 109/L (P<0.001). The PCT level of neonates in the study group (5.41±0.85) μg/L was higher than that of the reference group (0.24±0.07) μg/L (P<0.001). Conclusion: EONBI is closely associated with several obstetric high-risk factors, including preterm birth, fecal contamination of amniotic fluid, maternal infection during pregnancy, and premature rupture of membranes ≥18h.